Studi Analisis: Teori Pemrosesan Informasi dalam Pembelajaran PAI Berbasis HOTS - Nisa, Zakiyatul; Azzahra, Rahma Tiara; Khotimah, Siti Khorriyatul (Jurnal Ilmiah Dikdaya, 2023)
This research aims to examine the theory of information processing in Islamic Religious Education learning with a Higher Order Thinking Skills (HOTS) approach, focusing on improving students' critical thinking abilities. The research method used is a qualitative approach through literature review, with data sources such as books, journals, theses, and documents related to the theory of information processing in PAI learning based on HOTS. Data collection techniques involve observation and documentation. The results of this study showed that the theory of information processing in PAI learning based on HOTS have three main principles, namely the utilization of students' prior knowledge, goal-oriented instructional design, and feedback provision. In addition, there were several stages in the theory of information processing, namely stimulus identification as perception, response selection as decision-making, and response programming as action. The implementation of the theory of information processing in PAI learning based on HOTS can be done by presenting challenging statements to students to express arguments and engage in critical thinking. The application of the HOTS approaches also benefits students in developing logical and creative thinking skills, enabling them to become intelligent and skilled individuals.